2006
DOI: 10.1093/ps/85.5.932
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Suboptimal Eggshell Temperature During Incubation on Broiler Chick Quality, Live Performance, and Further Processing Yield

Abstract: Different incubation conditions can cause eggshell temperature (EST) to deviate from optimum. Two experiments were performed to determine the effect of low EST at the start of incubation and high EST at the end of incubation on hatchability, chick quality, 6-wk live performance, and breast meat yield of broiler chickens. In each experiment, 1,800 eggs from a single flock were divided and set into 2 setters. From 0 to 10 d of incubation, one setter was set to attain an EST of 36.6 degrees C (considered low), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 15 publications
4
44
1
2
Order By: Relevance
“…Willemsen et al (2010) reported that while cold incubated chicks had increased plasma T 3 and T 4 , there was no effect on body weights at DOH. In contrast, intermittent cold exposure of 15℃ at EA 18 and 19 (Shinder et al, 2009) and constant cold exposure of 36.6℃ from EA 1 to 10 increased chick weight (Joseph et al, 2006). We observed that lower serum free T 3 of T2 chicks from younger breeders was not associated with their body weight which was similar to that of T1, yet T2 chicks from older breeders were heavier and had numerically higher T 3 indicating an association between breeder age and response of those embryos to cooler incubation temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Willemsen et al (2010) reported that while cold incubated chicks had increased plasma T 3 and T 4 , there was no effect on body weights at DOH. In contrast, intermittent cold exposure of 15℃ at EA 18 and 19 (Shinder et al, 2009) and constant cold exposure of 36.6℃ from EA 1 to 10 increased chick weight (Joseph et al, 2006). We observed that lower serum free T 3 of T2 chicks from younger breeders was not associated with their body weight which was similar to that of T1, yet T2 chicks from older breeders were heavier and had numerically higher T 3 indicating an association between breeder age and response of those embryos to cooler incubation temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that incubation temperature influences embryo development and post-hatch performance (Lourens et al, 2005(Lourens et al, , 2007Meijerhof, 2009b;Molenaar et al, 2011). In studies that compared normal eggshell temperatures (approximately 37.8°C) to high shell temperatures (38.9 to 39.5°C), chick hatching weight was lower when eggs were incubated at high eggshell temperature at the end of incubation (Lourens et al, 2005;Joseph et al, 2006; (Hulet et al, 2007;Meijerhof, 2009b). Wineland et al (2000aWineland et al ( , 2000b) demonstrated that incubation temperatures above 37°C negatively affected the development of the whole body and specific organs of chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on this subject have usually compared the effects of lower or higher eggshell temperatures with optimal temperatures during early (4-7 days) (Shim & Pesti, 2011;Joseph et al, 2006) or late incubation (18-21 days) stages (Hulet et al, 2007;Leksrisompong et al, 2007;Willemsen et al, 2010) on different parameters (e.g., bone development and leg problems, embryo development, organ development, incubation parameters, chick quality, etc.). The aim of the present study was determine the effects of different eggshell temperatures (low, control, or high) applied between days 10 and 18 of incubation on broiler performance and susceptibility to ascites.…”
Section: Introductionmentioning
confidence: 99%
“…But, chick length was similar among groups, so the different hatcher temperatures did not affect the chick length at hatch. Similarly, Joseph et al (2006) found that higher temperature during hatching period resulted in lower chickhatching weight, but similar chick length compared to control. Similarly, in this study, chick length was similar in the treatment groups.…”
Section: Discussionmentioning
confidence: 80%